INTERFERENSI BAHASA INDONESIA KE DALAM BAHASA INGGRIS PADA ABSTRAK JURNAL ILMIAH - Any Budiarti Budiarti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
"> The research is aimed not only at the discussion on an interference ofIndonesian language into English language as shown in scientific journal abstracts butalso at the description on kinds of interference. There are 13 scientific journals that werestudied. The method applied in this research is descriptive with distributional andsimilarity analysis. The data is collected from abstracts of scientific journals during the year of 2003—2008. The results indicate that there are three kinds of interferences, namely: morphological, syntactic and semantic interferences. Morphology interferencehappens such as in verb form for the third person, plural form, and possessive. Syntactic interference includes the ill form of phrase and passive voice, paralellism, and the omission of to be and article. Semantic interference consists of addition and substitution